A facile route to regular and nonregular dot arrays by integrating nanoimprint lithography with sphere‐forming block copolymer directed self‐assembly. Issue 5 (7th December 2013) - Xiao, Shuaigang; Yang, XiaoMin; Hwu, Justin J.; Lee, Kim Y.; Kuo, David
ABSTRACT Nanoimprint lithography is used to create large‐area two‐dimensional prepatterns with tunable topographic heights in a resist layer. The resist prepatterns are applied to direct the self‐assembly of sphere‐forming polystyrene‐block‐polydimethylsiloxane block copolymers so as to form sparse nonregular nanodot arrays with flexible pattern layouts from high‐topography prepattern or dense regular nanodot arrays with a multiplicative pattern density from low‐topography prepattern. By precisely controlling the topographic height in substrate prepatterns, the origin of directed self‐assembly of block copolymer spheres using low‐topography prepattern is found to be topographic contrast. High‐fidelity pattern transfer from spherical block copolymer nanotemplates to functional materials indicates a promising route to ultrahigh density nanodevices. Bit‐patterned media over 1 teradot/in on a 2.5‐inch disk are fabricated, thus presenting future magnetic data storage media with great areal density growth potential. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 361–367